Chapter Una finestra aperta sull'Europa orientale: la Piccola biblioteca slava - Mazzitelli, Gabriele (Biblioteca di Studi Slavistici, 2019)
From 1928 to 1932 Italy's Istituto per l'Europa orientale (Eastern European Institute) published a book series entitled "Piccola Biblioteca Slava." This was not the first book series devoted to Slavic culture nor the last. Indeed, "Piccola Biblioteca Slava" closely resembles current practice at IPEO both for the quality of its collaborators and for the importance of the topics covered. As a whole, the series constitutes a concrete attempt to introduce Slavic literatures into Italian culture and it provides a unique source for reconstructing the history of Slavic studies in Italy.